The Effect of Family-Centered Affective Stimulation on Brain-Injured Comatose Patient’s Level of Consciousness Randomized Controlled Trial: A Literature Review - Rany Agustin Wulandari (D'Nursing and Health Journal (DNHJ), 2020)
Introduction: Traumatic brain injury is one of the most common causes of disability, death and intensive care unit (ICU) hospitalization worldwide. Each year an estimated ten million people experience brain injuries. All kinds of stimulation can effectively affect the brain, especially the reticular activation system. The aims to determine the effect of family-centered sensory stimulation by comparing the experimental, placebo and control groups. Method: This study used a randomized controlled trial involving comatose patients with brain injury. The investigators concluded that 30 patients were needed for each study group. Initially, an allocation protocol was developed using the permutation block randomization technique. Result: The one-way ANOVA results illustrated that the differences between groups regarding GCS scores on the first day and the second day of the intervention were not statistically significant, whereas on days 3-7, the differences were statistically significant. The results of this study indicate that early family-centered stimulation is more effective than sensory stimulation in correcting LOC among comatose patients with traumatic brain injury. Conclusion: Family-centered stimulation was effective in improving levels of consciousness among comatose patients from day three to day seven.